Nutcracker Syndrome: A Rare Cause of Hematuria - Emmanuel C. Gorospe; Michael O. Aigbe (The Scientific World Journal)
Nutcracker syndrome is the compression of the left renal vein between the aorta and superior mesenteric artery. It is a rare cause of hematuria which results from the rupture of congested renal veins into the collecting system.